Enhancing bedding hygiene in long-term care facilities: investigating the impact of multilevel antimicrobial polymers (MAP-1) on bacterial and MDRO reduction - Awais Farid; Wei Han; Joseph K.C. Kwan; King Lun Yeung (Antimicrobial Resistance and Infection Control)
Abstract Objective This study aims to assess the bactericidal efficacy of Multilevel Antimicrobial Polymer (MAP-1) on standard bedsheets in Long-term care facility (LTCF). The research quantifies total viable bacteria and MRSA counts and evaluates the percentage difference between treated and control bedding material over a one-week period. Design: A double-blind interventional, double cross-over study. Setting: Haven of Hope Woo Ping Care and Attention Home in Sai Kung, Hong Kong. Methods Over an 8-week period, bedding materials from residents’ rooms were sampled, totalling 288 samples from 96 bedsheets, with half treated with MAP-1 and the remaining serving as controls. MAP-1, developed at The Hong Kong University of Science and Technology, incorporates USFDA and USEPA-approved polymers. Sampling procedures adhered to standardized protocols, and bacterial counts were determined using culture methods. Data analysis employed t-tests and ANOVA to compare microbial loads between the control and treatment groups, with statistical significance set at p < 0.05. Results The study revealed a significant reduction in total viable bacteria and MRSA counts on bedsheets treated with MAP-1. Noteworthy reductions of 80.37% for total bacteria and 87.31% for MRSA at the end of seven-day use, in the intervention group compared to the control. These reductions were statistically significant across all four observation periods and among both male and female residents. Conclusion The study establishes the bactericidal efficacy of MAP-1 on standard bedsheets, showcasing its potential in diminishing total bacterial counts and MRSA contamination. These results hold promise for enhancing infection control practices and promoting improved sanitary conditions within healthcare settings.